Geometry and integrability - Mason, L. J. (Lionel J.); Nutku, Yavuz (London Mathematical Society lecture note series, 2003)
Based on a seminar for graduates held at the Feza Gürsey Institute, there are articles by some key researchers. One attractive feature is the inclusion of the algebro-geometric material as well as the twistor space methods, which form a bridge between the pure mathematics and the more physical approaches.